Own Attractiveness and Dissatisfaction With Physical Appearance Independently Predict the Salience of Facial Cues to Size When Women Judge Other Women's Attractiveness. (November 2017) - Watkins, Christopher D.
While facial cues to body size are a valid guide to health and attractiveness, it is unclear whether the observer's own condition predicts the salience of (low) size as a cue to female attractiveness. The current study examines whether measures related to women's own attractiveness/appearance predict the extent to which they use facial cues to size to differentiate other women on the attractiveness dimension. Women completed a body mass index (BMI) preference task, where they indicated their preference for high- versus low-BMI versions of the same woman, provided data to calculate their BMI and completed various psychometric measures (self-rated attractiveness/health, dissatisfaction with physical appearance). Here, attractive women and women who were dissatisfied with their own appearance were more likely to associate facial cues to low body size with high attractiveness. These data suggest that psychological factors related to women's appearance shape their evaluations of other women based on cues to size. Such variation in attractiveness judgements may function to reduce the costs of female competition for resources, for example, by identifying "quality" rivals or excluding others based on cues to size.